Five naphthalene-amide-bridged Ni(ii) complexes: electrochemistry, bifunctional fluorescence responses, removal of contaminants and optimization by CVD. Issue 8 (3rd February 2020) - Zhao, Jing; Luan, Jian; Yu, Huixuan; Liu, Guocheng; Lin, Hongyan; Wang, Xiuli; Chen, Baokuan
Abstract : Five multifunctional Ni-CPs based on a new naphthalene-amide and different carboxylates were obtained and exhibited various properties. CNTs were synthesized from the precursors of CPs, showing selective removal of contaminants in water. Abstract : To research the effect of carboxylates on the assembly of Ni(ii ) coordination polymers, a naphthalene-amide ligand L ( N, N ′-bis(pyridin-3-ylmethyl)naphthalene-2, 6-dicarboxamide) and five dicarboxylates [1, 4-H2 BDC = 1, 4-benzenedicarboxylic acid, 1, 4-H2 PDC = 1, 4-phenyldiacetic acid, 5-H2 HIP = 5-hydroxyisophthalic acid, 3, 4-H2 TDC = 3, 4-thiophenedicarboxylic acid, 2, 5-H2 TDC = 2, 5-thiophenedicarboxylic acid] were selected to combine with Ni(ii ) under hydrothermal conditions. Five coordination polymers [Ni(L )(1, 4-BDC)(H2 O)2 ] (1 ), [Ni(L )(1, 4-PDC)(H2 O)2 ] (2 ), [Ni(L )(5-HIP)(H2 O)2 ] (3 ), [Ni(L )(3, 4-TDC)(H2 O)2 ]·3H2 O (4 ) and [Ni(L )(2, 5-TDC)(H2 O)]2 ·3H2 O (5 ) were synthesized and structurally characterized by IR, PXRD and X-ray single-crystal diffraction. The title complexes show various structures: 2D 4-connected sql nets (1 and 2 ), a 3D cds framework of 3, 1D zigzag chain of 4 and 3D irl framework of 5 . The electrochemical behaviors of 1–5 and the solid-state luminescence and fluorescence responses of 5 to Fe 3+ and bovine serum albumin (BSA) were studied. Encouraged by functional thiophene components, 4 and 5 were used as catalyst precursors to synthesize carbon nanotubes (CNT-4 and CNT-5 ) by the chemical vapor deposition (CVD) method and characterized by XPS, SEM, TEM and Raman spectroscopy. The removals of contaminants (rhodamine B and Congo red) by 4 and 5 and their derivatives CNT-4 and CNT-5 in the aqueous phase were also comparatively investigated.